Comparison of the Effect of Dry Cupping Therapy and Acupressure at BL23 Point on Intensity of Postpartum Perineal Pain Based on the Short Form of McGill Pain Questionnaire - M Akbarzadeh; M Ghaemmaghami; Z yazdanpanahi; N Zare; A Mohagheghzadeh; A Azizi (JRI, 2016)
Background: Perineal pain is a major morbidity in the first few days after delivery. This study aimed to investigate the effect of dry cupping therapy and acupressure at BL23 point on the intensity of postpartum perineal pain based on the short-form of McGill pain questionnaire (SMPQ). Methods: The present clinical trial was conducted on 150 subjects in 3 groups of 50  cases. After at least 4-8 hr of delivery, cupping therapy was performed for 15-20 min up to 3 times a week (once a day) and acupressure was performed for 15-20 min based on clockwise model. The short-form of McGill pain questionnaire was completed both before and after the intervention. The SPSS statistical software was used to analyze the data using repeated measures ANOVA. Besides, p<0.05 was considered statistically significant. Results: In the cupping therapy group, mean of the perineal pain intensity reduced from 37.5±6.8 before the intervention to 11.1±6.1, 6.9±4.7, and 3.8±3.6 immediately, 24 hr, and 2 weeks after the intervention, respectively. The results of study showed that the differences between the intervention and control groups were statistically significant (p<0.01). Mean difference of the perineal pain intensity in the acupressure group reached from 35.6±8.1 before the intervention to 10.4±5.5 two weeks after the intervention, so the variation between intervention and control groups was statistically significant. Conclusion: The study findings showed that cupping therapy and acupressure reduced perineal pain. Therefore, they may be considered as effective treatments for reducing pain intensity of allowing delivery.